Bersiasat Melawan Saudara Tua: Mobilisasi dan Resistensi Perempuan Indonesia pada Masa Penjajahan Jepang - Keke Pahlevi Daradjati (Universitas Gadjah Mada, 2023)
The Japanese invasion of Indonesia in 1942 was driven by an urgent need for essential resources to support the Japanese effort to fight against the Allies. In its mobilisation plan, Japan placed women within the domestic sphere, providing daily informal services to support Japanese colonial policies. By analysing the Japanese propaganda materials and official documents chronologically, this paper found that there is the manipulation of several aspects of a gender policy for women, which were increasingly influenced by war conditions. Japan demands adherence to specific constructions about how women should act as citizens. In this regard, Indonesian women who chose collaboration and non-collaboration paths were adept at rearranging strategies so that the struggle continued as much as possible. To some extent, women could take advantage of the mass mobilisation facilities and roles that Japan had allocated to foster socio-economic improvements and efforts towards Indonesia’s political independence.